Quantitative body mass characterization before and after head and neck cancer radiotherapy: A challenge of height-weight formulae using computed tomography measurement. (October 2016) - Chamchod, Sasikarn; Fuller, Clifton D.; Mohamed, Abdallah S.R.; Grossberg, Aaron; Messer, Jay A.; Heukelom, Jolien; Gunn, G. Brandon; Kantor, Micheal E.; Eichelberger, Hillary; Garden, Adam S.; Rosenthal, David I.
Highlights: HNC patients lose significant lean and adipose tissue mass after radiation therapy. Formulae driven pre- and post-treatment LBM were significantly higher than calculated with CT. Height- and weight-based formulae fail to adequately approximate objective CT-based assessment. Abstract: Objectives: We undertook a challenge to determine if one or more height-weight formula(e) can be clinically used as a surrogate for direct CT-based imaging assessment of body composition before and after radiotherapy for head and neck cancer (HNC) patients, who are at risk for cancer- and therapy-associated cachexia/sarcopenia. Materials and methods: This retrospective single-institution study included 215 HNC patients, treated with curative radiotherapy between 2003 and 2013. Height/weight measures were tabulated. Skeletal muscle mass was contoured on pre- and post-treatment CT at the L3 vertebral level. Three common lean body mass (LBM) formulae (Hume, Boer, and James) were calculated, and compared to CT assessment at each time point. Results: 156 patients (73%) had tumors arising in the oropharynx and 130 (61%) received concurrent chemotherapy. Mean pretreatment body mass index (BMI) was 28.5 ± 4.9 kg/m 2 in men and 27.8 ± 8 kg/m 2 in women. Mean post-treatment BMI were 26.2 ± 4.4 kg/m 2 in men, 26 ± 7.5 kg/m 2 in women. Mean CT-derived LBM decreased from 55.2 ± 11.8 kg pre-therapy to 49.27 ± 9.84 kg post-radiation. Methods comparison revealed 95% limit of agreement of ±12.5–13.2 kg between CT and height-weight formulae. Post-treatment LBM with the three formulae was significantly different from CT (p < 0.0001). In all instances, no height-weight formula was practically equivalent to CT within ± 5 kg. Conclusion: Formulae cannot accurately substitute for direct quantitative imaging LBM measurements. We therefore recommend CT-based LBM assessment as a routine practice of head and neck cancer patient body composition.